Hydrogenation catalyst as well as preparation method and application thereof in room-temperature hydrogenation of unsaturated aromatic compound
By using core-shell structure multi-nanoalloys as catalysts in unsaturated aromatic compounds, the problem of lack of catalysts suitable for room temperature solvent-free hydrogenation in the prior art is solved, and efficient selective hydrogenation or co-hydrogenation reactions are achieved, reducing costs and ensuring catalytic activity.
Patent Information
- Application Number
- CN202411861415.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
There are no catalysts suitable for room temperature solvent-free hydrogenation in unsaturated aromatic compounds in the prior art.
A hydrogenation catalyst is provided including a core-shell structure multi-nanoalloy. The core-shell structure multi-nanoalloy consists of a core layer and a shell layer. The elements of the core layer include palladium, ruthenium, nickel, copper, silver, cadmium, iron, and cobalt. The elements of the shell layer include platinum, ruthenium, and rhodium. The catalyst is prepared by solvothermal reaction.
This catalyst can reduce the hydrogenation reaction energy barrier of unsaturated functional groups in unsaturated aromatic compounds, realize selective hydrogenation or co-hydrogenation at room temperature, reduce the cost of the catalyst and ensure catalytic activity.
Smart Images

Figure CN119680571A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic hydrogenation, and in particular to a hydrogenation catalyst and a preparation method thereof, and application of the catalyst in room temperature hydrogenation of unsaturated aromatic compounds. Background Art
[0002] Catalytic hydrogenation has important applications in the fields of petroleum, chemical engineering, medicine, and hydrogen energy. Examples include the synthesis of cyclohexanecarboxylic acid by hydrogenation of benzoic acid, the production of halogenated aromatic amines by catalytic hydrogenation of halogenated nitroaromatics, and the absorption of hydrogen in a closed environment by hydrogenation of solid unsaturated aromatic compounds.
[0003] Catalysts are crucial components of catalytic hydrogenation reactions, reducing the hydrogenation energy barrier and regulating reaction rate and selectivity. In the field of hydrogen absorption, catalysts are primarily used to irreversibly hydrogenate unsaturated organic molecules at room temperature and pressure, thereby reducing the concentration of hydrogen and its isotopes.
[0004] Commonly used unsaturated organic molecules are unsaturated aromatic compounds, including toluene, benzoic acid, p-chloronitrobenzene, 1,4-di(phenylethynyl)benzene, etc. However, there is currently no catalyst suitable for the room temperature solvent-free hydrogenation of unsaturated aromatic compounds. Summary of the Invention
[0005] The present invention aims to solve the problem that there is no catalyst suitable for room temperature solvent-free hydrogenation of unsaturated aromatic compounds in the prior art, and provides an application of a hydrogenation catalyst in room temperature hydrogenation of unsaturated aromatic compounds.
[0006] The technical method of the present invention is as follows:
[0007] A hydrogenation catalyst for room-temperature hydrogenation of unsaturated aromatic compounds, the hydrogenation catalyst comprising a core-shell multinary nanoalloy; the core-shell multinary nanoalloy comprising a core layer and a shell layer, wherein the core layer and the shell layer have different elements, the core layer comprising one or more of palladium, ruthenium, nickel, copper, silver, cadmium, iron, and cobalt, and the shell layer comprising one or more of platinum, ruthenium, and rhodium;
[0008] The unsaturated aromatic compound has an unsaturated functional group, and the unsaturated functional group includes one or more of a nitrogen-oxygen unsaturated bond, a carbon-oxygen unsaturated bond, and a carbon-carbon unsaturated bond;
[0009] The hydrogenation of the unsaturated aromatic compound is selective hydrogenation or co-hydrogenation of the unsaturated functional groups.
[0010] Optionally, among the elements of the shell layer, the molar ratio of each element to platinum is independently 0 to 1.5:1.
[0011] Optionally, among the elements of the core layer, the molar ratio of each element to platinum is independently 0 to 5:1.
[0012] Optionally, the hydrogenation catalyst further comprises a carrier, on which a core-shell structured multi-element nanoalloy is loaded; the carrier comprises one or more of carbon materials, metal oxides, boron nitride, montmorillonite, and metal skeletons.
[0013] Optionally, the loading mass percentage of the core-shell structure multi-element nanoalloy is 5% to 60%.
[0014] Optionally, the multi-component nanoalloy exists in the form of alloy particles; the particle size of the alloy particles is 1 to 40 nm.
[0015] Optionally, the nitrogen-oxygen unsaturated bond is a nitro group, the carbon-oxygen unsaturated bond includes one or more of a carbonyl group, an aldehyde group, and a ketone group, and the carbon-carbon unsaturated bond includes one or more of an alkenyl group, an alkynyl group, and a phenyl group.
[0016] The present invention also provides a method for preparing a hydrogenation catalyst, which comprises: mixing soluble compounds corresponding to the elements, a solvent, a reducing agent and a carrier according to the composition of the multi-element nanoalloy, and performing a solvent thermal reaction to obtain the hydrogenation catalyst.
[0017] Optionally, the solvent thermal reaction temperature is 150-400° C., the pressure is 0-4 MPa, and the time is 2-8 hours.
[0018] Optionally, the soluble compound includes one or more of soluble metal chlorides, soluble nitrates, soluble acetates, and soluble acetylacetonate metal salts; the solvent includes water and / or acetone; and the reducing agent includes one or more of alcohol, ascorbic acid, and sodium borohydride.
[0019] The beneficial effects of the present invention are:
[0020] 1) The present invention provides a hydrogenation catalyst for use in the room-temperature hydrogenation of unsaturated aromatic compounds. The hydrogenation catalyst comprises a core-shell multicomponent nanoalloy, comprising a core layer and a shell layer, wherein the core layer and the shell layer contain different elements. The core layer comprises one or more of palladium, ruthenium, nickel, copper, silver, cadmium, iron, and cobalt, and the shell layer comprises one or more of platinum, ruthenium, and rhodium. In the present invention, the core-shell multicomponent nanoalloy can reduce the hydrogenation reaction energy barrier of unsaturated functional groups in the unsaturated aromatic compound, thereby enabling the hydrogenation catalyst to achieve solvent-free co-hydrogenation or selective hydrogenation of the unsaturated aromatic compound at room temperature.
[0021] 2) The cheap elements in the core layer of the present invention reduce the cost of the hydrogenation catalyst, and the elements in the shell layer mainly play a catalytic role, thereby ensuring the catalytic activity of the hydrogenation catalyst.
[0022] 3) The preparation method of the hydrogenation catalyst of the present invention utilizes the difference in the reducibility of metal ions. Metals with higher mobility (Cu, Ni, Co, etc.) are preferentially reduced to form cores, while metals with lower mobility (Pt, Ru, etc.) are subsequently reduced to form shells. This preparation method is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the process for preparing hydrogenation catalyst using carbon nanofiber as a support;
[0024] Figure 2 TEM images and element distribution diagrams of the hydrogenation catalysts of Example 1 and Example 2; wherein, Figure 2 a is a TEM image of the catalyst of Example 1, Figure 2 b is the element distribution diagram of the catalyst of Example 1, Figure 2 c is a TEM image of the hydrogenation catalyst of Example 2, Figure 2 d is the element distribution diagram of the hydrogenation catalyst of Example 2;
[0025] Figure 3 TEM image and element distribution diagram of Example 3; wherein, Figure 3 a is a TEM image of the hydrogenation catalyst of Example 3, Figure 3 b is the element distribution diagram of the hydrogenation catalyst of Example 3;
[0026] Figure 4 The NMR analysis diagrams of the solid-state p-chloronitrobenzene hydrogenation process and before and after are shown. Figure 4 a is a schematic diagram of the hydrogenation process of p-chloronitrobenzene. Figure 4 b is the H NMR spectrum of p-chloronitrobenzene before and after hydrogenation. Figure 4 c is the NMR carbon spectrum of p-chloronitrobenzene before and after hydrogenation;
[0027] Figure 5 The gas chromatography-mass spectrometry analysis diagram of liquid p-chloronitrobenzene before and after hydrogenation;
[0028] Figure 6 The NMR analysis diagrams before and after the solid-state benzoic acid hydrogenation process are shown in Figure 2. Figure 6 a is a schematic diagram of the reaction process of benzoic acid hydrogenation. Figure 6 b is the H NMR spectrum of benzoic acid before and after hydrogenation. Figure 6 c is the NMR carbon spectrum of benzoic acid before and after hydrogenation;
[0029] Figure 7 The NMR analysis diagrams of liquid acetophenone before and after hydrogenation process are shown in Figure 1. Figure 7 a is a schematic diagram of the reaction process of acetophenone hydrogenation. Figure 7 b is the H NMR spectrum of acetophenone before and after hydrogenation. Figure 7c is the C NMR spectrum of benzaldehyde before and after hydrogenation. DETAILED DESCRIPTION
[0030] The following is a clear and complete description of the technical solution of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0031] The present invention provides an application of a hydrogenation catalyst in the room-temperature hydrogenation of unsaturated aromatic compounds, wherein the hydrogenation catalyst comprises a core-shell structured multinary nanoalloy. The core-shell structured multinary nanoalloy comprises a core layer and a shell layer, wherein the core layer and the shell layer have different elements, wherein the elements of the core layer comprise one or more of palladium, ruthenium, nickel, copper, silver, cadmium, iron, and cobalt, and the elements of the shell layer comprise one or more of platinum, ruthenium, and rhodium. The unsaturated aromatic compound comprises an unsaturated functional group, wherein the unsaturated functional group comprises one or more of a nitrogen-oxygen unsaturated bond, a carbon-oxygen unsaturated bond, and a carbon-carbon unsaturated bond. The hydrogenation of the unsaturated aromatic compound is selective hydrogenation or co-hydrogenation of the unsaturated functional groups.
[0032] It should be noted that the unsaturated aromatic compound of the present invention contains a benzene ring.
[0033] In one embodiment, the molar ratio of each element in the shell to platinum is independently 0 to 1.5: 1. For example, the molar ratio of each element to platinum can be independently 0 to 0.3: 1, 0.5 to 1: 1, or 0.9 to 1.5: 1.
[0034] In one embodiment, the molar ratio of each element in the core layer to platinum is independently 0 to 5:1. For example, the molar ratio of each element to platinum is independently 0 to 2:1, 1 to 4:1, or 1.5 to 3.5:1.
[0035] The elements of the core layer of the present invention are cheap elements, which reduces the cost of the hydrogenation catalyst. The elements of the shell layer mainly play a catalytic role, thereby ensuring the catalytic activity of the hydrogenation catalyst.
[0036] In one embodiment, the support comprises one or more non-porous or porous materials in the form of sheets, rods, layers, or spheres. Supports include inorganic supports, organic supports, and metal supports. Preferably, the inorganic support comprises a carbon material and / or boron nitride. Here, the carbon material includes graphite, carbon nanotubes, carbon nanofibers, etc. Preferably, the metal support comprises one or more metal oxides, montmorillonite, and metal skeletons.
[0037] In one embodiment, the loading mass percentage of the core-shell structured multi-element nanoalloy is 5% to 60%. For example, the loading mass percentage of the core-shell structured multi-element nanoalloy can be 6% to 40%, 10% to 50%, 20% to 40%, or 3% to 50%.
[0038] In one embodiment, the multi-element nanoalloy exists in the form of alloy particles. The particle size of the alloy particles is 1 to 40 nm, for example, 2 to 20 nm, 5 to 25 nm, 10 to 38 nm, 15 to 30 nm, or 18 to 37 nm.
[0039] Furthermore, the carrier may be carbon nanofibers modified with nitric acid. The preparation method of carbon nanofibers modified with nitric acid may adopt nitration pretreatment.
[0040] Specifically, the preparation method includes: ultrasonicating carbon nanofibers and nitric acid at room temperature for 1 to 3 hours, heating and refluxing at 90 to 110°C for 2 to 6 hours, cooling to room temperature, centrifuging at 6000 to 10000 rpm for 5 to 20 minutes, collecting the product, and then repeatedly washing the product with deionized water for multiple times, and freeze-drying for 30 to 60 hours to obtain nitric acid-modified carbon nanofibers.
[0041] The ratio of carbon nanofiber to nitric acid during ultrasonic treatment is 1g:1-4mol. Preferably, the ratio is 1g:1.46mol. The mass concentration of the nitric acid solution is preferably 14-16mol / L.
[0042] The freeze-drying time may be 30 to 60 hours, preferably 48 hours, and the freeze-drying temperature may be -55 to -80°C.
[0043] The reflux temperature is preferably 100° C., and the reflux time is preferably 4 h.
[0044] In the present invention, the oxygen-containing functional groups on the surface of the carbon nanofibers can be increased by nitration pretreatment, and defects can be generated at the same time, which is helpful for the dispersion of the catalyst.
[0045] The present invention also provides a method for preparing a hydrogenation catalyst, which comprises: mixing soluble compounds corresponding to each element, a solvent, a reducing agent and a carrier according to the composition of the multi-element nanoalloy, and performing a solvent thermal reaction to obtain the hydrogenation catalyst.
[0046] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0047] In one embodiment, the soluble compound includes one or more of a soluble metal chloride, a soluble nitrate, a soluble acetate, and a soluble metal salt of acetylacetonate. The solvent includes water and / or acetone. The reducing agent includes one or more of an alcohol, ascorbic acid, and sodium borohydride.
[0048] The present invention utilizes the different reducibility of metal elements to first reduce them into a core and then reduce them into a shell. This preparation method is simple and easy to operate. Here, the reducibility is affected by the reaction temperature, reaction speed, solution concentration, etc.
[0049] In one embodiment, the temperature of the solvothermal reaction is 150-400°C, the pressure is 0-3 MPa, and the time is 2-8 hours. For example, the temperature may be 180-280°C, 220-300°C, or 250-350°C. The pressure may be 0 MPa, 0-1 MPa, or 0-2 MPa. The time may be 2-6 hours, 3-7 hours, or 4-6 hours. Specifically, a solution containing a mixture of soluble compounds corresponding to each element, a solvent, a reducing agent, and a carrier is subjected to a solvothermal reaction with the carrier. Alternatively, the solvothermal reaction may be carried out under an inert gas. Here, the inert gas may be nitrogen or argon.
[0050] Here, the solvothermal reaction is preferably carried out in a hydrothermal reactor.
[0051] In one embodiment, the soluble compounds corresponding to the elements, the solvent, the reducing agent, and the carrier are mixed for 8 to 12 hours. Preferably, the mixing time is 10 hours. The mixing can be performed by stirring at a speed of 1000 to 1500 rpm. Preferably, the stirring speed is 1200 rpm.
[0052] In one embodiment, after the solvent thermal reaction, the present invention preferably further comprises cooling, separation, washing and drying in sequence. The present invention has no special limitation on the cooling process, and natural cooling to room temperature is sufficient. In the present invention, separation is preferably centrifugal separation; the rotation speed of the centrifugal separation is 7000-11000 rpm, preferably 8000 rpm, and the time is 5-15 min, preferably 10 min. In the present invention, the washing is preferably carried out in sequence with ethanol and acetone or ethanol and deionized water. The number of washings is preferably more than 3 times. In the present invention, the drying temperature is preferably 100°C and the drying time is preferably 8 hours.
[0053] When the carrier is carbon nanofiber, the process flow diagram provided by the present invention is as follows: Figure 1 shown.
[0054] In one embodiment, the unsaturated aromatic compound includes an aromatic compound having unsaturated functional groups, wherein the unsaturated functional groups include nitrogen-oxygen unsaturated bonds (nitro groups), carbon-oxygen unsaturated bonds (carbonyl groups, aldehydes, ketones, etc.), and carbon-carbon unsaturated bonds (alkenes, alkynes, phenyl groups) that have been selectively hydrogenated or co-hydrogenated.
[0055] In the present invention, the catalytic hydrogenation is carried out at room temperature.
[0056] The present invention is described in detail below by way of examples and experimental examples, which are merely illustrative and do not limit the present invention in any way.
[0057] Example 1
[0058] 1 g of carbon nanofibers and 100 mL of 14.6 mol / L nitric acid were ultrasonically mixed at room temperature for 1 h to make them uniformly mixed, heated to reflux at 100°C for 4 h, cooled to room temperature, and centrifuged at 8000 rpm for 10 min to separate and collect the product. The product was repeatedly washed three times with deionized water and freeze-dried for 48 h to obtain nitric acid-modified carbon nanofibers, which were recorded as CNFs.
[0059] 0.0412 g of platinum acetylacetonate, 0.0144 g of ruthenium acetylacetonate, 0.0094 g of copper acetylacetonate, 0.0095 g of nickel acetylacetonate, 0.0125 g of cobalt acetylacetonate (the concentration of each metal ion solution is 5 × 10 -4 mol / L) was added into 70 mL of ethanol-acetone mixed solution (volume ratio of 1:1), and ultrasonicated for 30 min at a power of 100 W to disperse uniformly to form a metal precursor solution.
[0060] 30 mg of nitric acid-modified carbon nanofibers were added to the precursor salt solution and stirred at 1200 rpm at room temperature for 10 hours to form a uniformly dispersed carbon nanofiber-metal precursor suspension. The suspension was then transferred to a 100 mL stainless steel autoclave and reacted at 180°C for 4 hours under a nitrogen atmosphere. After the reaction was completed, circulating water was passed through the autoclave for rapid cooling. After cooling to room temperature, the product was collected by centrifugation at 8000 rpm for 10 minutes, washed multiple times with ethanol and acetone, and dried under vacuum at 100°C for 8 hours to obtain the PtRuCuNiCo / CNFs catalyst.
[0061] Example 2
[0062] 0.0308 g of palladium acetylacetonate, 0.0405 g of platinum acetylacetonate, 0.0270 g of copper acetylacetonate, 0.0270 g of nickel acetylacetonate and 0.0411 g of ruthenium acetylacetonate (the ion concentration of each metal is 1×10 -3mol / L) was added into 100 mL of a mixed solution of ethanol and acetone (the volume ratio of acetone to ethanol was 1:1), and ultrasonicated at a power of 100 W for 30 min to form a metal salt precursor solution.
[0063] 2 mg of the nitrated pretreated carbon fibers (CNFs) obtained in Example 1 and 7 mL of the metal salt precursor mixed solution were mixed and stirred at room temperature at 1200 rpm for 10 h to form a carbon fiber-metal salt precursor suspension; the suspension was transferred to a 10 mL hydrothermal reactor and subjected to a solvent thermal reaction at 180°C for 6 h; the mixture was cooled to room temperature, centrifuged at 8000 rpm for 10 min, and the product was collected and washed several times with ethanol and acetone; and vacuum dried at 100°C for 8 h to obtain a PdPtRuCuNi / CNFs catalyst.
[0064] Example 3
[0065] 0.0304 g of platinum acetylacetonate and 0.0308 g of ruthenium acetylacetonate (the ion concentration of each metal is 7.5 × 10 - 4 mol / L) was added into 100 mL of a mixed solution of ethanol and acetone (the volume ratio of acetone to ethanol was 1:1), and ultrasonicated at a power of 100 W for 30 min to form a metal salt precursor solution.
[0066] 2 mg of nitric acid-modified carbon nanofibers (CNFs) obtained in Example 1 and 7 mL of the metal salt precursor mixed solution were mixed and stirred at room temperature at 1200 rpm for 10 h to form a uniformly dispersed carbon nanofiber-metal salt precursor suspension; the suspension was transferred to a 10 mL hydrothermal reactor and subjected to a solvent thermal reaction at 180°C for 4 h; cooled to room temperature, centrifuged at 6000 rpm for 10 min, the centrifuged product was collected, and washed several times with ethanol and acetone; and vacuum dried at 100°C for 12 h to obtain a PtRu / CNFs catalyst.
[0067] Example 4
[0068] 0.0363 g of chloroplatinic acid hexahydrate and 0.0287 g of ruthenium acetylacetonate (the ion concentration of each metal is 1×10 - 3 mol / L) was dissolved in a mixed solution of ethanol and deionized water (the volume ratio of ethanol to water was 1:1), and ultrasonicated at a power of 100 W for 30 min to form a metal salt precursor solution.
[0069] 30 mg of nitric acid-modified carbon nanofibers (CNFs) obtained in Example 1 were added to 70 ml of the metal precursor solution and stirred at room temperature at 1200 rpm for 10 h to form a uniform carbon nanofiber / metal precursor suspension. The suspension was transferred to a 100 mL stainless steel autoclave and reacted at 180 ° C for 4 h in a nitrogen atmosphere. After the reaction was completed, circulating water was passed through to rapidly cool the reaction. After cooling to room temperature, the product was collected by centrifugation at 8000 rpm for 10 min, washed multiple times with deionized water and anhydrous ethanol, and vacuum dried at 100 ° C for 8 h to obtain the PtRu / CNFs catalyst.
[0070] Example 5
[0071] 0.0778 g of chloroplatinic acid hexahydrate and 0.0615 g of ruthenium acetylacetonate were dissolved in 150 ml of a mixed solution of ethanol and deionized water (the volume ratio of ethanol to water was 1:1), and ultrasonicated at a power of 100 W for 30 minutes to form a metal salt precursor solution.
[0072] 60 mg of nitric acid-modified carbon nanofibers (CNFs) obtained in Example 1 were added to 150 ml of the metal precursor solution and stirred at 1200 rpm at room temperature for 10 hours to form a uniform carbon nanofiber / metal precursor suspension. The suspension was heated to 160°C and reacted for 6 hours. After cooling to room temperature, the product was collected by centrifugation at 8000 rpm for 10 minutes, washed multiple times with deionized water and anhydrous ethanol, and dried in vacuo at 100°C for 8 hours to obtain the PtRu / CNFs catalyst.
[0073] Comparative Example 1
[0074] 6 mmol of FeCl₃ was added to a 150 mL mixture of N-N-dimethylformamide and anhydrous ethanol (1:1 volume ratio) and magnetically stirred until the solid was completely dissolved. 4.5 mL of aqueous ammonia was added to the solution and the reaction was incubated at 60°C for 2 hours. Then, 3 mmol of terephthalic acid was added to the suspension and the reaction continued at 60°C for 6 hours. After cooling to room temperature, the suspension was filtered, washed, dried, and ground. The resulting sample, designated Fe-OCPs-2, was calcined at 700°C for 30 minutes (at a heating rate of 1°C / min) in a nitrogen atmosphere. The sample was then washed with 75 mL of 1 mol / L sulfuric acid for 5 hours, filtered, washed, and dried to obtain the Fe@C-2 catalyst.
[0075] Comparative Example 2
[0076] 1.017g of copper nitrate trihydrate and 1.5g of citric acid were added to 50mL of deionized water and stirred for 30 minutes to form a precursor solution. Then, 5.255g of tetraethyl orthosilicate was added and stirred at room temperature to form a gel. The gel was dried in an oven at 100°C for 12 hours and then calcined at 400°C in air for 5 hours (heating rate of 2°C / min). Finally, it was reduced at 300°C for 3 hours (in a 10% H2 / Ar gas mixture) to obtain the 15Cu@SiO2 catalyst.
[0077] Comparative Example 3
[0078] 2g of SBA-15 and 2g of glycine were dissolved in 200mL of a mixture of deionized water and anhydrous ethanol (deionized water and anhydrous ethanol, volume ratio: 1:1). Then, 10mL of a 0.85mol / L aqueous solution of Co(NO3)2·6H2O was added to form a pink suspension. The suspension was heated under reflux at 80°C for 12h, and then the solvent was removed by rotary evaporation at 70°C. The resulting powder was calcined at 800°C for 2h (5°C / min) in a nitrogen atmosphere. The SBA-15 template and Co nanoparticles were then etched with a 6mol / L NaOH solution at 60°C for 24h to form the Co1@NC-(SBA) catalyst.
[0079] Comparative Example 4
[0080] Ni(NO₃)₂·6H₂O, Mg(NO₃)₂·6H₂O, Al(NO₃)₃·9H₂O, and urea were dissolved in a 9:1 (volume ratio) mixture of ethylene glycol and water at a molar ratio of 2:0.5:1:16. After stirring for 30 minutes, the mixture was transferred to a 100 mL autoclave and reacted at 160°C for 6 hours. The resulting powder was filtered, washed several times with deionized water and ethanol, and dried in an oven at 100°C for 12 hours to obtain the NiMgAl-LDH precursor. Finally, the precursor was calcined at 500°C in static air for 8 hours to obtain the NiMgAl-MMO catalyst.
[0081] Comparative Example 5
[0082] 200 mg TiO2 and H2PtCl6 (4 mg Pt) were added to 50 mL of aqueous solution. After stirring at room temperature for 1 h, freshly prepared NaBH4 aqueous solution (2.3 mg, 0.2 mg mL) was slowly added. -1 ) and continued stirring for 1 hour. After the reaction, the solid was collected by filtration, washed three times with water and ethanol, and the powder was dried at room temperature for 12 hours. This yielded Pt / TiO2. The Pt / TiO2 was treated in an H2 atmosphere at 200°C (heating rate of 1°C / min) for 2 hours at a flow rate of 20 mL / min to obtain a Pt / TiO2-200 catalyst.
[0083] Comparative Example 6
[0084] 0.6 g of Nb2O5 and 8 mL of NaOH (5 mol / L) were added to 56 mL of ethylene glycol and ultrasonically dispersed for 5 minutes. The mixture was transferred to a 100 mL autoclave and reacted at 140°C for 12 hours. After cooling to room temperature, the product was collected by centrifugation, washed several times with deionized water and ethanol, and dried in an oven at 60°C for 12 hours to obtain the NaNbO3 support. 0.3 g of NaNbO3 and 60 mL of CH3OH were added to 240 mL of deionized water. Aqueous RhCl3 solution was added dropwise to the mixture. The solution was then vertically irradiated with a UV lamp (λ = 254 nm) for 1 hour under vigorous magnetic stirring. The product was collected by centrifugation, washed several times with deionized water and ethanol, and dried in an oven at 60°C for 12 hours to obtain the Rh / NaNbO3 catalyst.
[0085] Performance Testing
[0086] Test Example 1
[0087] The hydrogenation catalysts obtained in Examples 1-3 were tested using a transmission electron microscope, and the resulting TEM images are shown. Figure 2 a and 2b are the catalysts obtained in Example 1, Figure 2 c and 2d are the hydrogenation catalysts of Example 2; Figure 3 a and 3b are the catalysts obtained in Example 3. Figure 1 and 2 It can be seen that the multi-component alloy nanoparticles in the hydrogenation catalyst provided by the present invention are uniformly deposited on the surface of the carbon fiber, and the multi-component alloy nanoparticles all have a core-shell structure. The catalyst of Example 1 has Pt and Ru on the surface, and Cu, Ni, and Co inside. The catalyst obtained in Example 2 has Pt and Ru on the surface, and Pd, Cu, and Ni inside. The catalyst obtained in Example 3 has Pt on the surface and Ru inside. Based on this, it can be found that the catalyst preparation method of the present invention is suitable for preparing multi-component alloy nanoparticles with a core-shell structure.
[0088] Test Example 2
[0089] Liquid test: Add catalyst, reaction substrate and solvent into the reactor, introduce 1MPa nitrogen several times to remove air, introduce hydrogen several times to remove nitrogen, and finally adjust the hydrogen pressure to the specified pressure. After the reaction is completed, vent, open the reactor and collect the product, and detect and analyze it by gas chromatography-mass spectrometry.
[0090] Solid-state test: The catalyst and reaction substrate are fully ground in a certain mass ratio, added to the reactor after grinding, and 1MPa nitrogen is introduced multiple times to remove the air. Hydrogen is introduced multiple times to remove the nitrogen, and finally the hydrogen pressure is adjusted to the specified pressure. After the reaction is completed, the reactor is opened to vent and the product is collected, and then detected and analyzed by nuclear magnetic resonance.
[0091] (1) Figure 4 The NMR analysis diagrams before and after the solid-state hydrogenation of p-chloronitrobenzene show that characteristic peaks corresponding to amino groups appear in the hydrogen spectrum after the reaction. Carbon spectrum confirms that the product is p-chloroaniline. While the nitro group is hydrogenated, it can also ensure that no dehalogenation occurs, which shows extremely high selectivity.
[0092] (2) Figure 5 The gas chromatography-mass spectrometry analysis diagram of liquid p-chloronitrobenzene before and after hydrogenation shows that dehalogenation can be guaranteed even in the liquid phase, and the product has extremely high selectivity.
[0093] (3) Figure 6 The NMR analysis diagrams before and after the hydrogenation of solid-state benzoic acid show that the characteristic peaks corresponding to the benzene ring disappear after hydrogenation, and the characteristic peak corresponding to the carboxyl group shifts on the carbon spectrum, further proving that an addition reaction occurs on the benzene ring.
[0094] (4) Figure 7 The NMR analysis diagrams before and after the hydrogenation of acetophenone show that the characteristic peaks corresponding to the benzene ring disappear after hydrogenation, while the characteristic peaks corresponding to the carboxyl group shift, further proving that an addition reaction occurs on the benzene ring.
[0095] Table 1 Catalytic hydrogenation test results of the catalysts obtained in Examples 1 to 5 and Comparative Examples 1 to 6
[0096]
[0097] As can be seen from Table 1, the catalyst prepared by the present invention has extremely high activity and can achieve highly selective hydrogenation of p-chloronitrobenzene both in the presence and absence of solvents at room temperature; compared with the comparative example catalyst, it has a significant advantage in hydrogenation conditions. For benzoic acid, PdPtRuCuNi / CNFs and PtRu / CNFs prepared by varying the conditions can both achieve highly selective hydrogenation of the phenyl group in benzoic acid in the absence of solvents, with high activity and a significant advantage over the comparative example. For acetophenone, the PdPtRuCuNi catalyst prepared by the present invention can also achieve highly selective hydrogenation of the ketone group in acetophenone. Based on this, it can be found that the core-shell structure catalyst prepared by the present invention has significant advantages in the selective hydrogenation or full hydrogenation of aromatic compounds.
[0098] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. Application of a hydrogenation catalyst in room temperature hydrogenation of unsaturated aromatic compounds, characterized in that: The hydrogenation catalyst comprises a core-shell structure multi-element nano alloy; The core-shell structured multi-element nanoalloy comprises a core layer and a shell layer, and the elements of the core layer and the shell layer are different, the elements of the core layer include one or more of palladium, ruthenium, nickel, copper, silver, cadmium, iron, and cobalt, and the elements of the shell layer include one or more of platinum, ruthenium, and rhodium; The unsaturated aromatic compound has an unsaturated functional group, and the unsaturated functional group includes one or more of a nitrogen-oxygen unsaturated bond, a carbon-oxygen unsaturated bond, and a carbon-carbon unsaturated bond; The hydrogenation of the unsaturated aromatic compound is the selective hydrogenation or co-hydrogenation of the unsaturated functional groups.
2. The use according to claim 1, characterized in that: In the shell elements, the molar ratio of each element to platinum is independently 0 to 1.5:
1.
3. The use according to claim 1, characterized in that: In the core layer elements, the molar ratio of each element to platinum is independently 0 to 5:
1.
4. The use according to claim 1, characterized in that: The hydrogenation catalyst also includes a carrier, on which a core-shell structure multi-element nano alloy is loaded; The carrier includes one or more of carbon materials, metal oxides, boron nitride, montmorillonite, and metal skeletons.
5. The use according to claim 4, characterized in that: The loading mass percentage of the core-shell structure multi-element nano alloy is 5% to 60%.
6. The use according to claim 1, characterized in that: The multi-element nano alloy exists in the form of alloy particles; the particle size of the alloy particles is 1 to 40 nm.
7. The use according to claim 1, characterized in that: The nitrogen-oxygen unsaturated bond is a nitro group, The carbon-oxygen unsaturated bond includes one or more of carbonyl, aldehyde, and ketone. The carbon-carbon unsaturated bond includes one or more of alkene, alkyne, and phenyl.
8. A method for preparing a hydrogenation catalyst according to claim 1 to 7 for use in the room temperature hydrogenation of unsaturated aromatic compounds, characterized in that: The preparation method comprises: According to the composition of the multi-element nano alloy, the soluble compounds corresponding to each element, the solvent, the reducing agent and the carrier are mixed, and a solvent thermal reaction is carried out to obtain the hydrogenation catalyst.
9. The preparation method according to claim 8, characterized in that: The solvent thermal reaction is carried out at a temperature of 150 to 400° C., a pressure of 0 to 4 MPa, and a time of 2 to 8 hours.
10. The preparation method according to claim 8, characterized in that: The soluble compound includes one or more of soluble metal chlorides, soluble nitrates, soluble acetates, and soluble acetylacetonate metal salts; The solvent includes water and / or acetone; The reducing agent includes one or more of alcohol, ascorbic acid, and sodium borohydride.
Citation Information
Cited By
Multi-component ruthenium-nickel-based metal nanosheet as well as preparation method and application thereof
CN120394860A